Framework amidst the COVID-19 Pandemic: An Analytical Examination of Supervision Management Concepts - Murtado, Dodo (AIM: Journal of Islamic Education Management, 2023)
The oversight of educational institutions is of paramount importance in augmenting the caliber and efficiency of education, particularly in light of the profound challenges introduced by the Covid-19 pandemic. The repercussions of this global health crisis have permeated various sectors of society, with education being a notable focal point. The expeditious and extensive transmission of the Covid-19 virus mandates the adoption of customized approaches that align with the exigencies and constraints imposed by the ongoing pandemic. Therefore, this research endeavor is purposefully crafted to provide comprehensive insights into the metamorphosis of school supervision management paradigms amid the Covid-19 pandemic, specifically within the educational landscape. In the context of a pandemic scenario, the role of educational supervisors becomes increasingly crucial, as they play a pivotal role in facilitating meticulous planning, systematic organization, effective activation, adept management, rigorous control, skillful guidance, meticulous oversight, and continuous evaluation of distance learning processes. These processes are often facilitated through diverse platforms such as Zoom Meetings, WhatsApp Groups, Google Classroom, YouTube, and similar digital mediums. This strategic approach to addressing the repercussions of Covid-19 in the educational sphere necessitates the concerted collaboration of all stakeholders, encompassing governmental bodies, parents, educators, and educational institutions. It is undeniable that only through such collaborative endeavors can we ensure the seamless continuity of the educational process in the face of this pervasive pandemic.Â Â